La professionnalisation dans l'enseignement universitaire : un processus dialogique ? - Muriel Henry; Maryse Bournel Bosson
Professionalization in higher education in France is the subject of many debates about the goals and purposes of university degrees. This leads to a wide range of plans and actions, but the mechanisms behind have rarely been studied. After reviewing the questions raised by the main scientific approaches dealing with professionalization, this article analyses how it is implemented for professional bachelor degrees and what professors and programme directors think of, and do about it. Drawing on theory of activity - and in particular directed activity -, our conclusions emphasize the "dialogical universe" of activities, from course design to evaluation. In the same way, most of the activities offered to the students are designed in order to encourage them to analyse situations from different points of views. Professionalization can therefore be regarded as a dialogical process.